MODEL STRATEGI PRIORITAS PROGRAM PENGEMBANGAN KAPASITAS SDM PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN - Mochamad Asep Maksum; Dicky Iskandar Zulkarnain (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Preparing qualified human resources is one important aspect that needs to be considered in efforts to control forest and land fire. Forest and land fire control human resources, especially those at the site level are the spearhead in efforts to prevent and control forest and land fire in the field. The current human resource capacity development program is considered not optimal in supporting the forest and land fire control program effectively. This study aims to formulate a priority strategy for developing human resource capacity in supporting the effectiveness of forest and land fire control in Indonesia. The priority strategy model is developed through a systems approach by using Analytical Hierarchy Process method by involving interviews with several experts representing relevant stakeholders. This study concludes that the priority of the strategy in developing the capacity of human resources in forest and land fire control is through strengthening village/community-based institutional capacity. This study also indicates the need to optimize the role and involvement of local and village governments in increasing the capacity of human resources related to forest and land fire control on a village/community-based, and the need to prioritize the fulfillment of the input dimension compare to the process and output-outcome dimensions.